Pengaruh Keteraturan Senam Hamil terhadap Kualitas Tidur pada Ibu Hamil Trimester III di Desa Gedangsewupare Kediri: The Effect of Regular Exercise in Pregnancy on Sleep Quality in Third Trimester Pregnant Women in Gedangsewupare Village, Kediri - Rahayu, Dewi Taurisiawati; Hastuti, Nur Hardianti (Universitas Muhammadiyah Sidoarjo, 2018)
Sleep disturbances experienced by most pregnant women, how to overcome this is by doing regular and safe pregnancy exercises. This study aims to determine whether there is influence of pregnant gymnastics on sleep quality in pregnant women in the third trimester.This study used a pre-experimental method with the design of one group pre-test post-test. Total population of 15 third trimester pregnant women in Gedangsewu village on April 15 to May 14 2018 and the sample in this study were 13 respondents, using simple random sampling technique. Independent variables are pregnant gymnastics and the dependent variable is sleep quality. The instrument in the study was the PSQI questionnaire. Data analysis using Wilcoxon Sign Rank Test statistical test.Using the Wilcoxon Sign Rank Test statistical test, it was found that p = 0.000 or p <0.01 means that there was a significant difference in sleep quality in the pre-test with post-test III trimester pregnant women.Pregnant gymnastics has several benefits including eliminating complaints during pregnancy including sleep patterns. Pregnant women who regularly do pregnancy exercise, the muscles of the abdominal wall will be stronger so that the elasticity of the muscles of the abdominal wall can also be maintained so that it can adapt to changes during pregnancy.